Relationship between indirect measures of aerobic and muscle power with frequency speed of kick test multiple performance in taekwondo athletes - Albuquerque, M. R.; Tavares, L. D.; Longo, A. R.; Caldeira Mesquita, P. H.; Franchini, E. (International Journal of Sports Medicine, 2022)
This study aimed to determine the relationship between indirect measures of aerobic power and muscular power with Frequency Speed of Kick Test performance using multiple sets (FSKTmult) in high-level taekwondo athletes. We used a known-group method to test differences in FSKTmult performance between two groups designated as lower and higher performance in both aerobic power and muscular power. In total, 42 international or national taekwondo athletes of both sexes performed the FSKTmult, Progressive Specific Taekwondo Test (PSTT), and countermovement jump (CMJ). Our results showed that average of the three CMJ was moderately correlated with FSKTmult performance (r=0.44); whereas PSTT and FSKTmult were highly correlated (r=0.83). Moreover, the groups formed by lower and higher performance of time to exhaustion in PSTT, as well as the average of CMJ were able to discriminate performance in the FSKTmult (p =0.05). The present study thus suggests that aerobic and muscle power are important for FSKTmult performance.